The Dimensions Psychological Empowerment (Competence, Job Meaning, Independency, And Impact) And Their Influence On The Employees’ Effectiveness In The Iraqi Service Organizations - Hamady, Saad F. (Humanities Journal of University of Zakho, 2017)
The research aimed to determine the dimensions psychological empowerment (Competence, Job Meaning, Independency, and Impact) and their influence on the employees’ effectiveness in the Iraqi Service Organizations. The adopted research population consisted of three 5-star hotels and three private banks in Baghdad. To verify the hypotheses of the research, a questionnaire was used (including twenty-variable) to measure and reveal the aspect of the psychological empowerment to which departments in those hotels and banks from the perspective employees and using the five-Likert scale. The stepwise method was used to express the nature of empowerment dimensions impact in Job Satisfaction and Job Performance for Employees, SPSS software was implemented to extract the statistical results. The results showed awareness of each sample of hotels and banks regarding the psychological empowerment of individuals with a positive view of their relationship in these variables. It also showed that the most effective variables of the four mentioned above depends on the service they are offering whether it is banking service or hotels service. Stepwise decline analysis results showed from the answers of the hotel employees that the variables “Independency” and “impact” have the most effective contribution on job satisfaction and performance employees, while Competence and meaning it was not have any influence. But in the sample of banks showed that the results of the analysis “impact” and “meaning” have a clear influence on job satisfaction employees. While “meaning” and “Competence” to have a positive impact on the job performance employees. In addition to the variable “independence” of the four variables it did not have any active in influencing job satisfaction and performance from the perspective employees in the banking organizations. The research came to a set of conclusions and Proposals.